8-vinyl-deoxyadenosine, an alternative fluorescent nucleoside analog to 2′-deoxyribosyl-2-aminopurine with improved properties - Gaied, Nouha Ben (Oxford University Press, 2005)
We report here the synthesis and the spectroscopic characterization of 8-vinyl-deoxyadenosine (8vdA), a new fluorescent analog of deoxyadenosine. 8vdA was found to absorb and emit in the same wavelength range as 2′-deoxyribosyl-2-aminopurine (2AP), the most frequently used fluorescent nucleoside analog. Though the quantum yield of 8vdA is similar to that of 2AP, its molar absorption coefficient is about twice, enabling a more sensitive detection. Moreover, the fluorescence of 8vdA was found to be sensitive to temperature and solvent but not to pH (around neutrality) or coupling to phosphate groups. Though 8vdA is base sensitive and susceptible to depurination, the corresponding phosphoramidite was successfully prepared and incorporated in oligonucleotides of the type d(CGT TTT XNX TTT TGC) where N = 8vdA and X = A, T or C. The 8vdA-labeled oligonucleotides gave more stable duplexes than the corresponding 2AP-labeled sequences when X = A or T, indicating that 8vdA is less perturbing than 2AP and probably adopts an anti conformation to preserve the Watson–Crick H-bonding. In addition, the quantum yield of 8vdA is significantly higher than 2AP in all tested oligonucleotides in both their single strand and duplex states. The steady-state and time-resolved fluorescence parameters of 8vdA and 2AP were found to depend similarly on the nature of their flanking residues and on base pairing, suggesting that their photophysics are governed by similar mechanisms. Taken together, our data suggest that 8vdA is a non perturbing nucleoside analog that may be used with improved sensitivity for the same applications as 2AP.